Factors Controlling Velocity Variations at Short‐Term, Seasonal and Multiyear Time Scales, Ritigraben Rock Glacier, Western Swiss Alps. (22nd May 2017) - Kenner, Robert; Phillips, Marcia; Beutel, Jan; Hiller, Martin; Limpach, Philippe; Pointner, Eric; Volken, Martin
Abstract: This study analyses the factors controlling variations in short‐term, seasonal and multiyear deformation velocity of an alpine rock glacier from data obtained over periods of 1–20 years. The Ritigraben rock glacier, in the western Swiss Alps, was monitored using tacheometry, terrestrial laser scanning, an in situ global positioning system and borehole deformation measurements. Rock glacier stratigraphy and ground temperature data were obtained from boreholes, and long‐term meteorological data (temperature, precipitation, snow water equivalent) from nearby weather stations. Shearing within a distinct water‐bearing layer represents the major component of the displacement. Short‐term accelerations and seasonal velocity patterns of the rock glacier deformation appear to have been triggered by water supply to this layer. A long‐term acceleration of the rock glacier was probably also caused by increased water supply. Permafrost temperature in the rock glacier has increased slightly since 2002, yet no direct causality could be established between this limited warming and rock glacier acceleration. Copyright © 2017 John Wiley & Sons, Ltd.